Penggunaan Novel Sejarah Untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas XI IPS - Nahdatul Hazmi; Sri Ramadani (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT The purpose of the study was to determine the effect of increasing interest in learning and learning outcomes in history through the use of the historical novel Si Bung dari Siantar (Adam Malik) in class XI social studies at SMAN 1, Situjuah Limo Nagari sub-district. The research method used is a quasi-experimental research. The population in this study were all students consisting of 5 classes with a total of 137 students. The sampling technique was taken by purposive random sampling. The results showed that the data obtained were analyzed using the t-test, if-t(1-α) < t > t(1-α) then the hypothesis was accepted. With the results of his research data obtained t arithmetic = 3.91 and t table = 1.68 where - 1.68 <3.91> 1.68 which means the hypothesis is accepted within the 95% confidence level (α = 0.05). The conclusion of the study is that there is a positive effect on increasing interest in learning and learning outcomes of history through the use of the historical novel Si Bung dari Siantar (Adam Malik) in class XI social studies at SMAN 1, Situjuah Limo Nagari sub-district. Keywords: Historical Novels, Interests, Learning Outcomes.